**Who room the experts?**Our certified Educators are genuine professors, teachers, and scholars who use their scholastic expertise come tackle your toughest questions. Educators go with a rigorous application process, and also every prize they submit is the evaluation by ours in-house editorial team.

You are watching: Factor 4x^2-4x+1

move all terms no containing `x` to the right-hand next of the equation.

`4x^2-4x = -1`

To set the left-hand next of the equation equal to `0` , move all the expression to the left-hand side.

`4x^2-4x+1=0`

Remove the fraction by multiplying the an initial term that the element by...

Start her **48-hour cost-free trial** come unlock this answer and thousands more. Gain mmsanotherstage2019.com ad-free and cancel anytime.

Move all terms not containing `x` come the right-hand next of the equation.

`4x^2-4x = -1`

To set the left-hand next of the equation same to `0` , relocate all the expression to the left-hand side.

`4x^2-4x+1=0`

Remove the fraction by multiplying the an initial term the the variable by the denominator that the second term. `(2x-1)(2x-1)=0` collection each the the factors of the left-hand side of the equation equal to `0` . `2x-1=0` since `-1` does not contain the change to resolve for, move it to the right-hand next of the equation by including `1` to both sides. `2x=1` division each hatchet in the equation by `2` .

`x=1/2`

approved by mmsanotherstage2019.com Editorial Team

baxthum8

Educator because 2013

464 answers

| Certified educator

page Citation

Share connect

Factor: `4x^2 = 4 x-1`

`4x^2-4x + 1 = 0`

`(2x - 1)(2x-1) = 0`

The source is x = `1/2.`

authorized by mmsanotherstage2019.com Editorial Team

Tushar Chandra

Educator due to the fact that 2010

12,621 answers

| Certified educator

page Citation

Share attach

The equation 4x^2 = 4x - 1 has to be resolved for x.

Write the equation in the standard form of a quadratic equation ax^2 + bx + c = 0

4x^2 = 4x - 1

=> 4x^2 - 4x + 1 = 0

The polynomial 4x^2 - 4x + 1 has to be factored and also each the them equated to 0 to determine the root.

See more: A Ventilation Blower Should Be Operated For How Long After Fueling?

4x^2 - 4x + 1 = 0

Notice that 4x^2 = (2x)^2 and 4x = 2*2x*1. Substituting the very same gives: (2x)^2 - 2*2x*1 + 1^2 = 0

The left hand side is in the type a^2 - 2*a*b + b^2 i beg your pardon is equal to (a - b)^2

4x^2 - 4x + 1 = 0

=> (2x - 1)^2 = 0

=> x = 1/2

**The solution of the equation 4x^2 = 4x - 1 is x = 1/2**

authorized by mmsanotherstage2019.com Editorial Team

### Ask a Question

asking a concernSubmit inquiry

### Popular Questions

see all

## Related Questions

Browse everyMath

latest answer posted June 09, 2012 in ~ 5:56:48 afternoon

discover the root of 4x^2 + 7x + 3 = 0 using factorization.

1 educator answer

Math

recent answer posted November 17, 2011 at 2:15:03 am

how to integrate (1+4x^2)^(1/2)?

1 education answer

Math

latest answer post June 15, 2010 in ~ 3:46:09 to be

exactly how do u discover the square source of 1/2 * (square root of 8 + square root of 2)?

2 educator answers

Math

latest answer post August 24, 2014 in ~ 9:48:54 pm

one equation has actually roots 1 - i and 1 + i. What is the equation?

3 educator answers

Math

recent answer post November 08, 2015 at 7:42:37 am

`sqrt(x + 1) = x^2 - x` use Newton's technique to uncover all roots of the equation correct to 6 decimal places.

1 educator answer

mmsanotherstage2019.com will help you with any book or any question. Ours summaries and analyses room written by experts, and your questions are reply by genuine teachers. sign up with mmsanotherstage2019.com

use to be an education

### Recommended

### More

©2021 mmsanotherstage2019.com, Inc. All legal rights Reserved